Wound healing and gastroprotective effects of Clausena excavata leaves extract by modulating inflammation and oxidative stress / Shaymaa Fadhel Abbas Albaayit - Shaymaa Fadhel , Abbas Albaayit (2016)
Clausena excavata Brum. f. is an important traditional medicinal plant commonly used in Malaysia and South-East Asian countries for the treatment of many common ailments. However, the effect of C. excavata on wounds is not known. In this study, the wound healing and gastroprotective effects of C. excavata leaves extract were determined. Successive fractionation of leaves using petroleum ether (PT) followed by chloroform (CH), ethyl acetate (EA), and methanol (MOH) showed that MOH fraction possessed the highest total phenolic content of 522.0 ± 11.6 mg GAE/g plant extract. The ferric-reducing antioxidant power (FRAP) value of C. excavata MOH fraction was 4649 ± 11.3 μmol Fe2+/mg, while the radical scavenging activity using 2, 2-diphenyl-1-picryl dihydrazyl (DPPH) was 86.89 ± 1.4 % with IC50 at 23 μg/mL. The MOH fraction was innocuous against the human keratinocyte (HaCaT), macrophage (J77A.1), and Vero cell lines when assessed by the (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay. Further, the acute toxicity study on rats indicates treatment with MOH fraction even at a high dose of 5000 mg/kg body weight did not cause mortality. Further, MOH did not affect the kidney and haematological parameters or relative weights of the liver or kidneys at a high dose of 5000 mg/kg body weight. The in vitro scratch test demonstrated that MOH fraction at 100 μg/mL significantly stimulated proliferation and migration of fibroblast cells (p<0.05) at 24 and 48 hours after treatment shown by the faster closure of wound area compared to the untreated cells. Topical treatment of wound-induced Sprague-Dawley rats with 50, 100 and 200 mg/mL MOH fraction daily for 15 days was found to be effective in stimulating wound healing by decreasing wound size, improving wound contraction, enhancing tissue regeneration and granulation tissue, which were more significant (P<0.05) compared to the untreated control rats. The wound healing effect of MOH fraction is attributed to the significant (P<0.05) increase in transforming growth factor-beta (TGF-β1), vascular endothelial growth factor (VEGF), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and interleukine 10 (IL-10), while a significant (P<0.05) decreased in cyclooxygenase-2 (COX-2), tumor necrosis factor alpha (TNF-α), interleukine 6 (IL-6) and lipid peroxidation (LPO). Histological evaluations using the haematoxylin and eosin and Masson trichome stain methods showed that healed skin after treatment with MOH fraction had less scarring and greater fibroblast proliferation, collagen deposition, and angiogenesis compared to the untreated control. Besides, MOH fraction provoked apoptosis by the down-regulation of BAX gene and up-regulation of Bcl-2 gene. To determine the gastroprotective effect of MOH fraction, oral ethanol-induced gastric ulcer and the pylorus ligature rat model were used. The acid volume and pH of the gastric juice were determined in the pylorus ligature model. MOH fraction at dose 200 and 400mg/mL also showed significant (P<0.05) anti secretory effect of gastric juice in the stomach. Pre-treatment with MOH fraction significantly (P<0.05) increased SOD, GPx and CAT and reduced LPO activities. Increased expression of heat shock protein70 (HSP70) and transforming growth factor beta (TGF- β1) proteins occurred while decreased expression of BAX protein occurred in the stomach tissues of MOH fraction-treated rats. MOH fraction of C. excavata leaves extract decreased ulcer area and leucocyte infiltration and edema of the gastric submucosal layer, decreased volume, increased pH, and decreased total acidity of the gastric juice, showing that it is gastroprotective . MOH was characterized by LCMS/MS and shown to contain, myricetin glucoside, quercetin-rhamnose-hexose, kaempferol, furocoumarin, and 8-geranyloxy psoralen. In conclusion, MOH fraction facilitates wound healing and exhibits protective effects against gastric ulcers by stimulating activity of tissue antioxidant enzymes, thus preventing free radical-mediated tissue injury and modulating inflammatory mediators, and regulating apoptosis.